The fiscal compact and current account patterns in Europe - Stefan Behrendt (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2014)
This paper shall give an overview of the implications to the sectoral balances stemming from the implementation of the Fiscal Compact in the Euro area in 2013. Since there is noew a more or less strict limit to deficit spending - absent from cyclical factors - some other sector has to make up for the reduction of the financial deficit of Euro area governments. While applying sensible estimates on the trajectories of the sectoral balances in the Euro area, I reach the conclusion that the only logical outlet for these (potentially) reduced deficits would be the foreign sector, reflecting the inability of the private sector to run a sizable surplus of investments over savings over the long-run. Under the scenario described in the paper, the Euro area would run a considerable current account surplus in the foreseeable future.
Keywords: E27; E61; E62; E66; F32; H62; H63; 330; fiscal policy; Fiscal Compact; current account; sectoral balances